Distinct Cecal and Fecal Microbiome Responses to Stress Are Accompanied by Sex- and Diet-Dependent Changes in Behavior and Gut Serotonin - Lyte, Joshua M.; Koester, Lucas R.; Daniels, Karrie M.; Lyte, Mark (Frontiers in Neuroscience, 2022)
Although diet- and stress-induced perturbations in the microbiome associate with changes in host behavior via the microbiota-gut-brain axis, few mechanisms have been identified. The identification of causative pathways by which the microbiome influences host behavior therefore would benefit from the application of evidence-based conceptual frameworks. One such causal framework is microbial endocrinology which is the study of neuroendocrine axes as avenues of bi-directional neurochemical-based host-microbe crosstalk. As such, we investigated the relationship between diet- and stress-induced alterations in behavior, regional gut serotonergic response, and concomitant changes in the cecal and fecal microbiomes of male and female mice. Our results demonstrate that sex is a dominant factor in determining compositional changes in the gut microbiome in response to stress and diet modifications. Intestinal serotonergic responses to stress were observed in both sexes but dietary modifications uniquely affected region-specific changes in males and females. Likewise, behavioral alterations diverged between male and female mice. Together, these results demonstrate distinct sex-dependent relationships between cecal and fecal microbial taxa and behavioral- and serotonergic-responses to stress and diet. The present study demonstrates the importance of including both male and female sexes in the examination of the microbiota-gut-brain axis. As different microbial taxa were identified to associate with the behavioral and gut serotonergic responses of male and female mice, certain bacterial species may hold sex-dependent functional relevance for the host. Future investigations seeking to develop microbiome-based strategies to afford host stress resilience should include sex-based differences in the microbiome.